ANALISIS PENGARUH PEMBERDAYAAN DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi pada Karyawan PDAM Tirta Moedal Kota Semarang) - Ayuningtyas, Aditya Hapsari; Djastuti, Indi (Faculty of Economics and Business Diponegoro University, 2017)
Employee empowerment and career development are important factor in the company survival in order to achieve the goals of a company which is to increase productivity and produce the quality of human resource perfomance. The aim of this research is to test and analyze the influence of empowerment to job satisfaction, the influence of career development on job satisfaction, the influence of empowerment to the employee performance, the influence of career development on employee performance, the influence of job satisfaction on employee performance, the influence of empowerment to the employee’s performance with job satisfaction as intervening variable and the influence career development on employee performance with job satisfaction as intervening variable.The population of this research are employees of PDAM Tirta Moedal Semarang City as many as 504 people. The target population of this study are permanent employees with a working period more than two years and undergraduate education (S1). So the sample of 122 respondents. The analysis used is multiple linear regression analysis method. The data testing technique used is the path analysis test, where the analysis includes: validity test, reliability test, classical assumption test, t test, F test, coefficient determination test and sobel test to the mediation effect. The results of analysis, this study result that empowerment and career development proved to have a positive and significant impact on job satisfaction. Then empowerment and career development have a positive and significant impact to the employee performance. While job satisfaction have a positive and significant impact to the employee performance. Job satisfaction mediates the effect of empowerment with a small value to employee performance. In addition, job satisfaction mediates the effect of career development with small value on employee performance.